Foveal avascular zone: differences between two different acquisition protocols - Anacleto, Inês (2023)
OCT-A is an exam that allows visualization of the retinal and choroidal vascularization as well as the three-dimensional visualization of the vascular plexuses at different depths, providing functional information about the blood flow in the vessels, and areas of non-perfusion or neovascularization. The foveal avascular zone corresponds to an area deprived of capillaries in the foveolar region that can be detected and measured using OCT-A. When performing the exam, it is possible to choose between two methods with different resolution and acquisition times, so it is important to assess whether the measurements are comparable between methods. The objective of this study was to see if there are differences in the measurement of the foveal avascular zone between two different OCT-A scanning protocols. The conducted study was a case-control cross-sectional study. The sample consisted of 26 participants with diabetes mellitus. The instrument used was the SD-OCT HRA+OCT SPECTRALIS Heidelberg Engineering. The patient assessment consisted of collecting 10° x 10° high-resolution and 20° x 20° high-speed OCT-A scans. These were manually measured by two observers, who each took two measurements of the foveal avascular zone of each scan (high-speed and high-resolution) in each complex (superficial and deep). Statistical analysis was performed using the SPSS program. There were no statistically significant differences between the different measurements, and it can be stated that the evaluation of the two protocols is repeatable and reproducible, with good agreement between the methods. However, the use of both retinal plexuses together to evaluate the foveal avascular zone may be more appropriate.